The Impact of Risk Management Efficiency on Organizational Performance in State-Owned Enterprises and the Mediating Ef-fect of Supply Chain Maturity: Evidence from Morocco - Benkirane Kawtar; Benazzi Khadija (Qubahan Academic Journal, 2025)
While numerous studies have explored the influence of effective risk management on performance, the specific dynamics within state-owned enterprises (SOEs), particularly in developing nations like Morocco, remain less understood. This study investigates the interactions between risk management effectives, supply chain maturity and both the financial and social dimensions of performance within Moroccan public commercial offices (OMPAM). The main objective of this article is to study the impact of formalized risk management practices on the organizational performance of Moroccan public offices with commercial activities. As well as the impact of integrated risk management on the organizational performance of public offices and subsequently show the role of the mediating variable which is the maturity of the supply chain on the relationship between the effectiveness of risk management and the organizational performance of public offices. Data were collected from 140 managerial employees across five Moroccan public commercial offices. Data was analyzed using Partial Least square Method on SPSS and Bootstrapping on SmartPLS, because these two tools are effective and provide reliable results in management science research. We mobilized also the non-probability "snowball" sampling technique to generate much more response due to the difficulties of accessing respondents in this sector. The results reveal that risk management positively influences organizational performance, which is partially confirmed. Concretely, the formalization of risk management practices is supported, while integrated risk management shows a negative effect on the organizational performance of public offices, contradicting our expectations, which reflects on the one hand the weak relationship between the two variables with a negative student T of -6.040. Moreover, we conclude also that the maturity of the supply chain exerts a mediating effect between the efficiency of risk management and the level of performance in Moroccan public offices with commercial activities. These interactions seem to diverge from the initial model when studying each of the financial and the social dimensions each on its own. The study's limitations include potential biases in self-reported data, a limited number of factors considered in the model, and the specific context of Moroccan public sector organizations, which may limit the generalizability of the findings. The study underscores the importance of formalizing risk management practices and developing mature supply chains to improve organizational performance in public sector enterprises. Policymakers and managers should focus on these areas to enhance the resilience and efficiency of SOEs in Morocco. Further research should explore the contextual factors affecting these relationships and develop tailored strategies for different organizational environments.